2018
DOI: 10.1002/uog.17505
|View full text |Cite
|
Sign up to set email alerts
|

24‐segment sphericity index: a new technique to evaluate fetal cardiac diastolic shape

Abstract: Determination of SI for each of 24 segments of the fetal right and left ventricles provides a comprehensive method to examine the shape of the ventricular chambers. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
155
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 77 publications
(164 citation statements)
references
References 30 publications
3
155
4
2
Order By: Relevance
“…Once the analysis for each ventricle was completed, the raw data were exported to an ASCII text file. The text file was imported into an Excel spreadsheet (Microsoft Corporation, Redmond, WA) that had been programed to convert the X and Y pixel coordinates of the end‐systolic and end‐diastolic locations for the first (lateral wall) and 48th (septal wall) segments for each ventricle as previously described (Figure C) . The pixel length from the end‐diastolic and end‐systolic apex of each ventricle to the end‐diastolic and end‐systolic position of the midpoint of the lateral (segment 1) and septal (segment 48) segments was computed and converted to millimeters (Figure ) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Once the analysis for each ventricle was completed, the raw data were exported to an ASCII text file. The text file was imported into an Excel spreadsheet (Microsoft Corporation, Redmond, WA) that had been programed to convert the X and Y pixel coordinates of the end‐systolic and end‐diastolic locations for the first (lateral wall) and 48th (septal wall) segments for each ventricle as previously described (Figure C) . The pixel length from the end‐diastolic and end‐systolic apex of each ventricle to the end‐diastolic and end‐systolic position of the midpoint of the lateral (segment 1) and septal (segment 48) segments was computed and converted to millimeters (Figure ) .…”
Section: Methodsmentioning
confidence: 99%
“…The text file was imported into an Excel spreadsheet (Microsoft Corporation, Redmond, WA) that had been programed to convert the X and Y pixel coordinates of the end‐systolic and end‐diastolic locations for the first (lateral wall) and 48th (septal wall) segments for each ventricle as previously described (Figure C) . The pixel length from the end‐diastolic and end‐systolic apex of each ventricle to the end‐diastolic and end‐systolic position of the midpoint of the lateral (segment 1) and septal (segment 48) segments was computed and converted to millimeters (Figure ) . The longitudinal displacement fractional shortening was computed by the following formula (Figure C): longitudinal displacement fractional shortening = [(enddiastolic length endsystolic length)/enddiastolic length]×100. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in left ventricular (LV) and right ventricular (RV) size and function have been reported in various fetal disease states . In prior studies, we have reported using speckle‐tracking software to evaluate various parameters of the fetal LV and RV, including the area, 24‐segment transverse widths, 24‐segment transverse fractional shortening, fractional area change, as well as longitudinal basal‐apical contractility and displacement . These measurements reported from our group have not yet been applied postnatally.…”
mentioning
confidence: 99%